Ben Yokoyama and the cookies of chaos - Swanson, Matthew, 1974- (Swanson, Matthew, 1974- Cookie chronicles, 2023)
While attempting to return a lost wallet to its owner, Ben tries out different life philosophies inspired by his friends, family, and fortune cookies.